IMPLEMENTING NDN USING SDN: A REVIEW ON METHODS AND APPLICATIONS - Rowshanrad, Shiva; Parsaei, Mohamad Reza; Keshtgari, Manijeh (IIUM Engineering Journal, 2016)
In recent years many claims about the limitations of todays’ network architecture, its lack of flexibility and ability to response to ongoing changes and increasing users demands. In this regard, new network architectures are proposed. Software Defined Networking (SDN) is one of these new architectures which centralizes the control of network by separating control plane from data plane. This separation leads to intelligence, flexibility and easier control in computer networks. One of the advantages of this framework is the ability to implement and test new protocols and architectures in actual networks without any concern of interruption. Named Data Networking (NDN) is another paradigm for future network architecture. With NDN the network becomes aware of the content that is providing, rather than just transferring it among end-points. NDN attracts researchers’ attention and known as the potential future of networking and internet. Providing NDN functionalities over SDN is an important requirement to enable the innovation and optimization of network resources. In this paper first we describe about SDN and NDN, and then we introduce methods for implementing NDN using SDN. We also point out the advantages and applications of implementing NDN over SDN.